Diversity and composition of bacterial communities associated with healthy and bleached coral Fungia sp. in Nha Trang bay, Vietnam - Van Ngoc, Bui; Nhat Huy, Chu (Vietnam Journal of Biotechnology, 2022)
Coral bleaching is probably caused by the loss of endosymbiotic algae from the host tissue or disturbance of the microbial community composition of corals. In particular, bacteria inhabiting the surface mucus layer of corals are supposed to mediate coral health, but their role in coral bleaching has not been fully clarified. In the present study, we collected mucus samples from bleached and healthy Fungia sp. colonies in Nha Trang bay to investigate biodiversity and bacterial community composition using 16S rRNA gene amplicon next-generation sequencing. The results indicated rich biodiversity and significant changes in bacterial communities between bleached and healthy corals. Two phyla, Proteobacteria and Bacteroidetes, making up approximately 80% of the total bacterial abundance, were predominant in both bleached and healthy samples. Three phyla, Actinobacteria, Planctomycetes, and Cyanobacteria identified as minor taxa, were low in abundance in both samples. However, there were significant differences in bacterial communities at the genus level. Three bacterial genera, Erythobacteria, Synechcococcus CC9902, and Candidatus Actinomarina, involved in coral health protection, were mostly determined in the healthy coral samples. Whereas, five genera, Algicola, Fusibacter, Halodesulfovibrio, Marinifilum, and especially the genus Vibrio, were mainly detected in the bleached corals with a notable increase in relative abundance. Moreover, analysis of alpha and beta diversity (NMDS) also confirmed that there were significant changes in bacterial composition between the bleached and healthy corals (p-value <0.05). These findings suggest that the disturbance of the bacterial community composition living on coral is one of the factors causing coral bleaching, beside environmental factors like pH, temperature, and dissolved oxygen.